Efeitos dos glicocorticóides sobre os limiares da reação de defesa induzida pela estimulação elétrica da matéria cinzenta periaquedutal dorsal de ratos - Rangel, Tathiana Corrêa (2007)
Prelimminary results (Vargas, 2002) showed that after 3 hours peripheral injections of dexamethasone (DEXA) caused a reduction in the thresholds of DPAG-evoked immobility. In contrast, DPAG-evoked micturition thresholds were raised. Because DEXA is supposed to suppress the hypothalamus-pituitary-adrenal (HPA) axis peripherally. The present study evaluated the effect of intracerebroventricular (i.c.v.) injections of DEXA (0.8 µg /15 µL, n=20), corticosterone (CORT, 40 µg /15 µL, n=20) or salina (NaCl 0,9%, 15 µL, n=20) on the thresholds of the defense reaction induced by electrical stimulation of DPAG, as well as by the exploration behaviour in the elevatedplus-maze (EPM), a sensitive equipment the changes the anxiety. Rats which stimulation induced gallops or jumps with less than 85 µA were submitted to 4 stimulation sessions with sine-wave increasing intensities (0-90 µA, 60 Hz, a.c.) in 3 consecutive days: Day 1 - control, Day 2 - 15 min and 3 h after the central injection of DEXA, CORT or salina, Day 3 – washout. The EPM performance was assessed in the Day 2, 1.5 h after its administration. The thresholds median (I50±SE) of responses of immobility (IMM), exophthalmus (EXO), trotting (TRT), galloping (GLP), jumping (JMP), micturition (MIC) e defecation (DEF) were compared through likelihood ratio tests (P< 0.05, Bonferroni’s criterion). The DEXA facilitated JMP (∆I50= -16.8 %), they attenuated GLP (∆I50=17.1% 15 minutes and 31.2% after 24 hours) and DEF (∆I50=22.3%). Whereas the CORT had similar effects on JMP (∆I50= -14.3% after 3 hours) and GLP (∆I50=17.8% 15 minutes and 13.8% after 3 hours), but facilitated DEF (∆I50= -31.4% after 3 hours) and MIC (∆I50= -29.3% after 15 minutes). The salina attenuated MIC (∆I50=12.3% 15 minutes and 42.2% after 3 hours) and the IMM (∆I50=13.5% after 24 hours), but the responses DEF and MIC were virtually aboliteds after 3 h. Remaining defensive responses were not changed significantly. Nobody of the drugs produced an anxiolytic-like effect significant by the open-arm and close-arm exploration in the EPM. Although, the treatments were the effect significant by the exploration in the central platform. Compared with the salina, these effects were due the marked reduction of exploration in the central platform by CORT. A significant reduction was observed too, after injections of DEXA. Glucocorticoids diverse effects on MIC and DEF were most likely due to their distinct affinity for type- I and II receptors. Because DEXA present 14 results were the opposite of the previous studies with peripheral injections, the latter results should be ascribed to the peripheral suppression of HPA axis and ensuing reduction in CORT plasma levels. GLP attenuation was most likely due to its replacement by JMP, which thresholds were significantly facilitated. The decrease in JMP thresholds is compatible with the stress facilitation of panic attacks. Although panic attacks do not activate the HPA axis, there are evidences of the hyperactivity of HPA axis in panic disorder. Likewise to panic attacks, DPAG stimulation does not activate the HPA axis. Nevertheless, stress-induced increases in HPA axis activity are likely to influence the functioning of DPAG.